Pengakuan dan Perlindungan Hukum Terhadap Eksistensi Pemerintahan Adat - Jenny Kristiana Matuankotta (SASI, 2020)
The existence of Customary Law Communities in Indonesia, including Customary Law Communities in the State of Eti, West Seram Regency is a fact in the life of the nation and the State in the Unitary State of the Republic of Indonesia. The existence of the Customary Law Community, including its Customary Government system, should also receive legal recognition and protection in accordance with constitutional recognition as regulated in the 1945 Constitution of the Republic of Indonesia Article 18B Paragraph (2). The results of the research show that although the existence of constitutional communities has been recognized constitutionally by the State, the implementation of regional policies related to the recognition and protection of indigenous peoples including their customary government has not been recognized in regional regulations that contain such recognition.